Analysis of inductor-converter bridge by means of state-space averaging technique (superconducting magnet energy storage) - Bilgiç, Mehmet Oruç; Ehsani, M. (My University, 1988)
The time-averaged behavior of an inductor-converter bridge (ICB) circuit has been analyzed using a state-space averaging technique. The application of the state-space averaging technique to the ICB circuit analysis is somewhat different from the well known DC-to-DC converter cases such as buck, boost, and flyback of Cuk converter analysis in that the first-order approximation of the state transition matrix will give trivial results. The results, which were previously obtained in infinite Fourier series form, are in closed form. A comparison is also made with the Fourier result. The ICB is a two-quadrant power supply for superconductive energy storage magnets. Closed-form expressions are found for the average current, voltage, and power behavior of the ICB. This application is somewhat different from the analysis of other DC choppers such as buck, boost, flyback, and Cuk converters in that the first-order terms are identically zero and the second-order terms have to be used.
Keywords: Converter; State-Space Averaging Technique; Magnetic analysis; Superconducting magnets; Energy storage; Matrix converters; Bridge circuits; Circuit analysis; DC-DC power converters; Fourier series; Power supplies; Superconductivity